IMPLEMENTASI MANAJEMEN ARSIP DINAMIS PADA UNIT ADMINISTRASI RUMAH SAKIT RSUD MATARAM - Ardiyanna; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Records management is an important aspect in the hospital administration system. This is because there are many files that should be stored and can be recovered so that the patient's track record can be systematically traced and the personnel files can be stored properly. The goal to be achieved in this research is an analysis of archive management services at the Mataram Regional General Hospital (RSUD) and what factors influence it. The research method uses a qualitative approach to the type of descriptive research. Data collection techniques using observation and interviews. The results of the study show that archive management procedures at Merauke Hospital have not been running well. This is because the archive storage system does not meet the standards, namely the incorporation of the archive room with the service room and the application of the archive cycle in the Administrative Office of Mataram Hospital has not been understood by employees. In addition, there are still many archives that accumulate due to the insufficient manber of filing cabinets. In the archive storage stage, a standard storage system has been used, namely using an alphabetical system, date, month, year and subject and region. Thus, the suggestions that can be given are to make an archive storage so that if needed it can be found again, add facilities and infrastructure in the archive field at the Mataram Hospital Administration office such as adding a filing cabinet, making your own archive room, doing regular archive shrinkage, and maintenance archives should be improved again by making a routine schedule for administrative staff employees.